DEVELOPMENT OF POCKET BOOKING AND SETTLEMENT FOR PREVENTION OF BULLYING IN THE MIDDLE SCHOOL BENGKULU CITY - Widdya Elsa Pratiwi; Bambang Sahono (UNIB Press, 2019)
The aim of this study was to: 1) Describe the development of pocket guidance and counseling books for the prevention of bullying in Bengkulu City High School, 2) Describe the effectiveness of the guidance and counseling pocket book for prevention of bullying in Bengkulu City High School, the research method used the ADDIE model. consists of five main stages, namely (A) nalysis, (D) esign, (D) evelopment, (I) implementation, and (E) valuation, which is used to analyze data from expert validation, namely design experts, linguists, and guidance and counseling expert with 25 research subjects. The results of this study are: a) The feasibility assessment by material experts is obtained in the Very Eligible category. Students' responses to the existence of a guidance and counseling pocket book for prevention of bullying in Bengkulu City High School for small group trials included in the very low category and for the experimental class test in the very high category and in the control class included in the low category. The pocket book of guidance and counseling for the prevention of bullying in the High School of Bengkulu City is very effective for students 'knowledge and can increase students' knowledge about preventing bullying.